PENGARUH APLIKASI TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP DAYA SAING UKM - Ratnamurni, Elis Dwiana; Irawan, Andri (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2018)
Small and medium enterprises (SMEs) play an important role and strategic for the country's economic growth in both developing and developed countries. Increasing competitiveness is determined by the carrying capacity, science and technology, innovation ability and the learning process that develops in the community. The aim of this research is to examine the application of Information and Communications Technology Business and Competitiveness of SMEs Effect on Food and Beverages in Cimahi. This research is descriptive and exploratory and using quantitative research approach and explanatory survey method. There are 100 Small and Medium Business Unit which deploy in 15 villages in Cimahi taken as sample using stratified random sampling technique. Data are collected based on interviews and questionnaires. According to the discussion, this research obtain results as follows : a. SMEs Cimahi majority (75.17%) already use information technology applications to market their products, although at 24.83 percent do not use any type of information technology applications. Applications predominantly used are Facebook, BBM, SMS and Instagram. b. Cimahi city SMEs largely use information technology to market their products. But there are still constraints faced by them; limited knowledge and ability of the management of SMEs to apply information and communication technologies in accordance with the demands of technology and the development of times. c. Application of information technology and business communication partially no effect on the competitiveness of the SME Food and Beverages in Cimahi, but simultaneously, impact on their competitiveness. Thus, they need to implement decision making, which related to the application of information technology, and business communication jointly. Recommendations for the Government of Cimahi are as follows: enhance further programs that support the competitiveness of SMEs of Cimahi among products of SMEs in other cities. Expanding SMEs’ opportunities to increase understanding of the importance of Communication Technology Applications for SMEs as well as facilitating the access of SMEs to be able to market their products online by providing supportive training.